Are They Ready? Trials, Tribulations, and Professional Skills Vital for New Veterinary Graduate Success - Reinhard, Addie R.; Hains, Kristina D.; Hains, Bryan J.; Strand, Elizabeth B. (Frontiers in Veterinary Science, 2021)
Stress and burnout levels are high among young veterinarians with the transition to practice being particularly challenging. This qualitative study aimed to capture and document the new graduate veterinary experience within the United States and which professional skills are most important for success during the transition to practice. The researchers sought to better understand this challenging transition period and provide insight for veterinary educators who are tasked with preparing new veterinary graduates for day one practice readiness. To gain a deeper understanding of the new graduate experience, a focus group was conducted with six veterinarians who recently graduated from four different U.S. veterinary colleges. Several themes arose regarding their experiences in the transition to practice including setbacks and adaptations, self-sufficiency and self-doubt, changing clientele and ethical dilemmas, leadership and conflict, and good vs. bad mentorship. Self-care, conflict management, and client communication were perceived as the most important professional skills for success in the transition to practice. New graduate veterinarians reported that they were least prepared for working with clients with financial constraints and managing conflict. Drawing from this qualitative data, the researchers propose several topics that could be incorporated into professional skills curriculum to further enhance day one preparedness of new veterinary graduates to promote well-being in the transition to practice.